2011
DOI: 10.1590/s1516-89132011000600016
|View full text |Cite
|
Sign up to set email alerts
|

The effect of phosphoethanolamine intake on mortality and macrophage activity in mice with solid ehrlich tumors

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…The general information of the selected articles is presented in Tables I and II. Several studies of PHOS-S have been performed. This substance has been linked to anticarcinogenic effects and reportedly alters the cell metabolism of the immune response (Arruda et al, 2011), elicits antitumor effects (Ferreira et al, 2011(Ferreira et al, , 2012a(Ferreira et al, ,b, 2013a, induces apoptosis in cells (Ferreira et al, 2011(Ferreira et al, , 2012a(Ferreira et al, ,b, 2013a, elicits antileukemic effects (Ferreira et al, 2013c), possesses antiangiogenic (Ferreira et al, 2013b) and antimetastatic activity (Ferreira et al, 2011(Ferreira et al, , 2013b, and, conversely, stimulates tumor proliferation (KanoSueoka et al, 1979).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The general information of the selected articles is presented in Tables I and II. Several studies of PHOS-S have been performed. This substance has been linked to anticarcinogenic effects and reportedly alters the cell metabolism of the immune response (Arruda et al, 2011), elicits antitumor effects (Ferreira et al, 2011(Ferreira et al, , 2012a(Ferreira et al, ,b, 2013a, induces apoptosis in cells (Ferreira et al, 2011(Ferreira et al, , 2012a(Ferreira et al, ,b, 2013a, elicits antileukemic effects (Ferreira et al, 2013c), possesses antiangiogenic (Ferreira et al, 2013b) and antimetastatic activity (Ferreira et al, 2011(Ferreira et al, , 2013b, and, conversely, stimulates tumor proliferation (KanoSueoka et al, 1979).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the histopathology of the excised tumors showed greater cell cohesion of tumor cells retrieved from mice treated with PHOS-S (Arruda et al, 2011).…”
Section: Alterations In the Cells Of The Immune Responsementioning
confidence: 97%
See 2 more Smart Citations
“…In six articles, Chierice and coworkers reported the effects of syn-phospho on cytotoxicity and xenograft tumor rodent assays. [5][6][7][8][9][10] It is of note that in five of these six studies the authors did not declare the purity of the test compound, [5][6][7]9,10 and in one study they informed that syn--phospho (analyzed by high-performance liquid chromatography) was 99% pure. 8 A Nuclear Magnetic Resonance (NMR) analysis conducted by an independent laboratory (University of Campinas -Unicamp) contracted by the Ministry of Science Technology and Innovation (MCTI), however, found that phosphoethanolamine accounted for only 32.2% of the so-called "synthetic" phosphoethanolamine.…”
mentioning
confidence: 99%